2019
DOI: 10.1155/2019/3907915
|View full text |Cite
|
Sign up to set email alerts
|

Design, Preparation, and Characterization of Dioscin Nanosuspensions and Evaluation of Their Protective Effect against Carbon Tetrachloride-Induced Acute Liver Injury in Mice

Abstract: The purpose of this study was to prepare a dioscin nanosuspension (Dio-NS) that has a better distance and high solubility for oral administration and to evaluate its hepatoprotective effects. Optimal primary manufacture parameters, including shear time, shear speed, emulation temperature, pressure, and cycles of homogenization, were determined by single-factor experiments. The concentrations of dioscin, SDS, and soybean lecithin were optimized using the central composite design-response surface method, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…116,141 6.1.1 | Acute liver damage More than half of all acute liver injuries are caused by adverse drug reactions, or certain toxic chemicals or drugs such as carbon tetrachloride (CCl 4 ), alphanaphthyl-isothiocyanate (ANIT), dimethylnitrosamine (DMN), paracetamol, and lipopolysaccharide (LPS). 116,141 CCl 4 , ANIT, DMN, LPS, and ethanol have been used in in vitro models to monitor the activity of different medications against acute liver damage. Multiple studies have confirmed the role of dioscin in reducing the serum levels of alanine aminotransferase (ALT) and aspartate transaminase (AST) to improve liver conditions via the effects of dioscin in ameliorating oxidative stress, inflammation, and apoptosis.…”
Section: Hepatoprotective Mechanisms Of Dioscinmentioning
confidence: 99%
See 3 more Smart Citations
“…116,141 6.1.1 | Acute liver damage More than half of all acute liver injuries are caused by adverse drug reactions, or certain toxic chemicals or drugs such as carbon tetrachloride (CCl 4 ), alphanaphthyl-isothiocyanate (ANIT), dimethylnitrosamine (DMN), paracetamol, and lipopolysaccharide (LPS). 116,141 CCl 4 , ANIT, DMN, LPS, and ethanol have been used in in vitro models to monitor the activity of different medications against acute liver damage. Multiple studies have confirmed the role of dioscin in reducing the serum levels of alanine aminotransferase (ALT) and aspartate transaminase (AST) to improve liver conditions via the effects of dioscin in ameliorating oxidative stress, inflammation, and apoptosis.…”
Section: Hepatoprotective Mechanisms Of Dioscinmentioning
confidence: 99%
“…The liver is a major organ in the human body and it plays a critical role in regulating synthetic and metabolic processes such as detoxification and assimilation. It can be frequently exposed to extreme stress and undergo pathological changes in response to the stress, which may lead to potentially life‐threatening liver damage, 106 including diseases such as hepatitis, fibrosis, cirrhosis, cholestasis, HCC, hepatic ischemia, or other injuries that result in hepatic disorders and acute or chronic liver failure 116,141 …”
Section: Defense Against Organ Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Liver disease is common and often life-threatening. 1 Carbon tetrachloride (CCl 4 ), 2 paracetamol 3 and lipopolysaccharide 4 may cause acute liver injury. The occurrence of liver injury may be related to viral infection, alcohol and drugs.…”
Section: Introductionmentioning
confidence: 99%